MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL SNOWBALL THROWING SISWA SEKOLAH DASAR NEGERI 023 MUARA MAHAT BARU - Vina Desri Rama Putri; Afriza Rahma Rani; Romi Laspita; Kasman Edi Putra; Fadhilaturrahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low reading comprehension skills in Indonesian language learning among fifth-grade students at SD 023 Muara Mahat Baru, Kampar Regency. One solution to address this issue is the implementation of the snowball throwing learning model. The purpose of this study is to improve students’ reading comprehension skills in Indonesian language lessons. The research method used is Classroom Action Research (CAR), conducted in two cycles, with each cycle consisting of two meetings and four stages: planning, implementation, observation, and reflection. The research was carried out in September 2025. The subjects of the study were 25 fifth- grade students, consisting of 13 boys and 12 girls. The data collection techniques used were documentation and observation. Before the action was taken, students’ cooperation ability was 36%. After the first cycle, it increased to 48%, and in the second cycle, it rose to 92%. Thus, it can be concluded that using the snowball throwing model can improve reading comprehension skills in Indonesian language learning for fifth-grade students at SD 023 Muara Mahat Baru, Kampar Regency. Keywords : Reading Comprehension, Snowball Throwing Model